Design & modeling of phase transforming ultra-high temperature metal ceramic multilayer composites - Stotts, John Carter, author; Weinberger, Christopher R., advisor; Gelfand, Martin, committee member; Ma, Kaka, committee member; Sambur, Justin, committee member (Colorado State University. Libraries, 2025)
Ultra-high temperature ceramics are a class of materials that have found use in high-temperature structural applications due to their high melting temperatures and excellent high-temperature mechanical properties. Although this class of materials is well-suited to these applications at high temperature, they suffer from a low fracture toughness at ambient temperatures where component fabrication and assembly takes place. Thus, during the fabrication and assembly process these materials are highly susceptible to catastrophic brittle failure. In this work, we introduce a novel type of composite that significantly improves the low-temperature fracture toughness without sacrificing the excellent high-temperature properties of the ultra-high temperature ceramics. These novel composites are an innovative approach to metal-ceramic multilayer composites, with the unique ability undergo a phase transformation in the metal layers that results in their disappearance, leaving a single-phase ultra-high temperature ceramic after annealing. In this work, we endeavored to model this phase transformation process and characterize the performance of the composite in order to optimize the material selection and design of the composite. To achieve this goal, we determined the phase transformation time of composites using Finite Element Method simulations and constructed more general, coarse-grained, models of the phase transformation kinetics and toughening. The key to enabling the phase transformation in these composites is to choose group IV transition metal carbides or nitrides and group V transition metal carbides for the ceramic layers of the composite. This group of materials possess a wide range of homogeneity with respect to carbon/nitrogen content in their monocarbide/nitride phases. Additionally, the phase transformation from metal to ceramic in these materials is controlled by the diffusion of the nonmetal atom (carbon/nitrogen) and results in ceramic layer growth with strong adhesion between layers. Thus, a composite can be constructed with a 'frozen-in' non-equilibrium microstructure containing alternating layers of metal and ceramic and be made to transform simply by increasing the temperature, i.e. annealing. Furthermore, this work contains an investigation into the kinetics of carbon diffusion in substoichiometric titanium carbide. This investigation, motivated by an open question in the literature posed by Sarian in 1968, used a computational approach comprised of Monte Carlo, kinetic Monte Carlo, and Density Functional Theory simulations in order to determine the interconnection of diffusion and vacancy-ordered phases. The investigation was multi-pronged, beginning with simulations on a square lattice and then being extended to three-dimension simulations of the titanium carbide carbon-vacancy sublattice.
Keywords: diffusion; hypersonics; ultra-high temperature ceramics; high temperature materials; composites; phase transformations